Genetic counseling student rotations in industry: How COVID‐19 magnified the urgency for virtual learning options in diverse training settings. Issue 5 (30th August 2021) - Arjunan, Aishwarya; Sanders, Merideth; Chen, Anthony; Roscow, Breanna; Ray, Jessica
Abstract: The COVID‐19 pandemic created unprecedented challenges worldwide that required rapid adaptation and transformation across the entire healthcare system. Graduate medical training programs across all specialties have moved to rapidly adjust to the virtual landscape. This created a unique opportunity for genetic counselors who work in industry and within diagnostic laboratories to develop internship and rotation programs that can be offered virtually to meet the needs of genetic counseling training programs. Myriad Genetics, Inc., was contacted by numerous graduate programs in genetic counseling beginning in March 2020 requesting the opportunity for their students to participate in remote laboratory‐based rotations. As a result of these requests, a working group of genetic counselors across Myriad came together to adapt existing experiences to fully remote formats and develop new remote‐based opportunities for students. We describe our experience of expanding genetic counseling student rotations during the COVID‐19 pandemic with the goal of providing examples of remote learning experiences that may be applicable to other diagnostic laboratory industry‐based rotations for genetic counseling students. In 2020, a total of 59 second‐year genetic counseling students, from 21 different genetic counseling training programs, participated in one of five different virtual experiences. Furthermore, two new rotation experiences were created to increase capacity and highlight diversity of industry roles. Genetic counselors in industry are uniquely positioned to provide both remote training opportunities for genetic counseling students and exposure to the variety of roles that genetic counselors can occupy. Increasing the exposure to these roles is important as the genetic counseling workforce continues to expand and diversify, and it is imperative among all programs to enable access to these opportunities.